The Impact of Health Education Through Audio-Visual Media on Increasing Knowledge of Type 2 Diabetes Prevention Among Students - Andi Fajriansi; Auliyah Usriani Lukman; Suarnianti (Ammar Dharma Foundation, 2025)
Background: Type II Diabetes Mellitus continues to rise globally, especially among adolescents, who often lack awareness of the risks associated with this disease due to insufficient information.Objective: This study aims to evaluate the impact of health education using audio-visual media on increasing knowledge of Type II Diabetes Mellitus prevention among 11th-grade students at SMA Negeri 23 Makassar.Methods: The research used a pre-experimental design with a one-group pre-test and post-test approach. A total of 138 respondents were randomly selected from a population of 212 students. Data were collected using a questionnaire and analyzed using the Wilcoxon Signed Rank Test.Results: The study found a significant improvement in the knowledge of Type II Diabetes Mellitus prevention after receiving health education through audio-visual media, with a ???? value of 0.000. Conclusion: Health education through audio-visual media significantly enhances the knowledge level regarding the prevention of Type II Diabetes Mellitus among 11th-grade students at SMA Negeri 23 Makassar.